2022
DOI: 10.1136/bmjgh-2022-008880
|View full text |Cite
|
Sign up to set email alerts
|

Community prevalence and dyad disease pattern of multimorbidity in China and India: a systematic review

Abstract: Background Driven by the increasing life expectancy, China and India, the two most populous countries in the world are experiencing a rising burden of multimorbidity. This study aims to explore community prevalence and dyad patterns of multimorbidity in China and India. Methods We conducted a systematic review of five English and Chinese electronic databases. Studies involving adults 18 years or older at a community level, which reported multimorbidity prevalence and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 74 publications
0
17
0
5
Order By: Relevance
“… 2 , 3 , 4 Due to a lack of data from low-income countries and the use of different definitions of multimorbidity, a recent systematic review highlighted the need to estimate the prevalence of multimorbidity and patterns of multimorbidity. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 , 4 Due to a lack of data from low-income countries and the use of different definitions of multimorbidity, a recent systematic review highlighted the need to estimate the prevalence of multimorbidity and patterns of multimorbidity. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 14 , 16 , 17 , 18 , 19 Two systematic reviews on multimorbidity identified depression, hypertension, and diabetes as the most prevalent co-occurring chronic diseases. 5 , 20 Another study of multimorbidity identified cardiovascular and metabolic diseases as the most common diseases, followed by mental health disorders and musculoskeletal conditions. 21 In a multi-national cross-sectional study of non-institutionalized adults aged 50 and over in Finland, Poland, Spain, China, Ghana, India, Mexico, Russia, and South Africa, hypertension, cataract, and arthritis were the most prevalent comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while comorbidity is more prevalent in the community than trials, among those with comorbidity, the pattern of correlations were mostly similar. Although a number of studies have examined patterns of comorbidity in the community, [4][5][6] or looked at excluded comorbid conditions in trials. 20 This is the first study of which we are aware to examine patterns of comorbidity in trials, or to compare comorbidity patterns between trials and the community.…”
Section: Discussionmentioning
confidence: 99%
“…With ageing of population, the prevalence of multimorbidity (defined as the coexistence of 2 or more NCDs in one person) is increasing among older adults. In a systematic review, the median prevalence of multimorbidity was 30.7% among all people in China, and it was about half of the prevalence among older adults [ 11 13 ]. Such a severe disease burden directly triggers a high amount of medical expenditure and CHE incidence.…”
Section: Introductionmentioning
confidence: 99%